A preliminary study on the feasibility of community game-based respiratory muscle training for individuals with high cervical spinal cord injury levels: a novel approach - Dongheon Kang; Jiyoung Park; Seon-Deok Eun (BMC, 2022)
Abstract Background Respiratory disorders result in rehospitalization and premature death of patients with cervical spinal cord injuries (CSCI). Community game-based respiratory muscle training (RMT) programs could reduce secondary complications. Methods We examined the feasibility and preliminary efficacy of RMT as a community-based exercise program. Among the 10 included participants (eight male and two female), four, one, one, and four reported C3, C4, C5, and C6 complete injuries, respectively (eight graded by American Spinal Injury Association impairment scale [ASIA] A and two by ASIA B). Their mean age was 43 ± 12.3 y. The time since injury was 10 ± 6.7 y. The participants completed an RMT program for 60 min/day, twice weekly, for 8 weeks. The participants were trained in the use of a newly developed game-based RMT device. The device provides consistent pressure for respiratory muscle strength and endurance training. Seven RMT devices were modified to allow 10 game-based RMT programs. Forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), peak expiratory flow (PEF), vital capacity (VC), inspiratory capacity (IC), inspiratory reserve volume (IRV), expiratory reserve volume (ERV), maximum inspiratory pressure (MIP), maximum expiratory pressure (MEP), and peak cough flow (PCF) were measured. Results There were improvements after RMT compared to pre-RMT in FVC (p = 0.027, 10.62%, 0.22 effect size [ES]), PEF (p = 0.006, 23.21%, 0.45 ES), VC (p = 0.002, 35.52%, 0.60 ES), IC (p = 0.001, 46.94%, 0.81 ES), IRV (p = 0.001, 90.53%, 1.22 ES), MIP (p = 0.002, 97.25%, 1.32 ES), MEP (p = 0.005, 141.12%, 1.07 ES), and PCF (p = 0.001, 35.60%, 0.74 ES). The participants reported a positive impact of the program. Conclusions Community game-based RMT for individuals with CSCI appears to be safe and feasible. Community exercise with RMT use may have a positive impact on the respiratory measures for patients with CSCI who are vulnerable to respiratory compromise. Trial registration KCT0005980.